DOES DEPRESSION ASSOCIATED TO PERSISTENT AUDITORY HALLUCINATIONS RESPOND TO NURSE LED SELF SYMPTOM MANAGEMENT STRATEGIES?- A CASE STUDY INVESTIGATION - J.B Bivin; Sailaxmi Gandhi; John P John (Indian Journal of Psychiatric Nursing)
Medication resistant persistent auditory hallucinations are pervasive in patients with schizophrenia. Efficacy of nurse- led self symptom management strategies is evident in the literature from western settings; though its efficacy has not been tested in Indian settings. This study aimed at examining the effects of teaching self symptom management strategies on distressing parameters and depression secondary to PAH. A case study method was adopted to measure the effectiveness of teaching self symptom management strategies in a patient with a diagnosis of Paranoid schizophrenia on distressing parameters and depression secondary to PAH. Measurements were done at baseline, immediately after each session and weekly follow up for one month. Baseline measurements were done using Auditory Hallucination Interview Guide, as a screening tool, Characteristics of Auditory Hallucination Questionnaire and Beck Depression Inventory-II. Immediately after and follow up levels of measurement were done using CAHQ and BDI-II. Therapeutic response was defined as the reduction of the CAHQ and BDI-II scores. The post and follow up measurement showed reduction in characteristics of auditory hallucination sub-scores and overall depression score when compared to the baseline scores. The study concluded that teaching self symptom management strategies are effective in reducing both the distressing parameters of PAH and depression secondary to it.